Some Motets in Honour of St Joseph in the Archives of the Ursulines of Québec - Schwandt, Erich (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1996)
There is a handful of motets in honour of one of New France's most important patrons—St Joseph—preserved at the Archives of the Ursulines of Québec. This group of eight motets has formed the basis of speculation about the musical gifts of Père René Ménard and Mère Marie de St Joseph. Both of them are mentioned in 1640 as being capable musicians, but both were dead by the middle of the seventeenth century. In this article the St Joseph motets are examined to see if there is any basis for connecting any of the music to either person. Unfortunately, all of the music is stylistically much too late to have been composed by Père Ménard, or to have been assembled or copied by Mère de St Joseph. Solum nomen super est.